Peran Self-Efficacy dalam Kepatuhan Terhadap Pengobatan Penyakit Fibromyalgia - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Milna Sari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Fibromyalgia is a chronic disorder characterized by widespread muscle pain and fatigue, often accompanied by psychological symptoms such as anxiety and depression. Medication adherence is crucial for managing this condition, yet many patients struggle to follow prescribed regimens. This study aims to explore the role of self-efficacy in medication adherence among fibromyalgia patients through a systematic review and meta-analysis. The researcher conducted a literature search in major electronic databases to identify relevant studies published between 2015 and 2023. Out of 1,247 identified articles, 18 studies met the inclusion criteria and were eligible for analysis. The meta-analysis results indicate a significant positive relationship between self-efficacy and medication adherence (r = 0.42, 95% CI [0.35, 0.49], p < 0.001). Moderator analysis revealed that this relationship is stronger among patients receiving self-efficacy-based interventions compared to those receiving standard care. These findings underscore the importance of integrating self-efficacy enhancement strategies into fibromyalgia management to improve medication adherence, ultimately leading to better patient health outcomes.